2016
DOI: 10.1016/j.jcf.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a palliative care curriculum for cystic fibrosis healthcare providers

Abstract: CF-specific palliative care training was well received by participants and significantly improved self-assessed comfort with core skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 30 publications
(40 reference statements)
0
41
0
Order By: Relevance
“…Longer and more rigorous PC training/curriculum has been developed for CF providers and has focused on symptom management and difficult conversations; these sessions were well received by participants and (2) significantly improved self-assessed comfort with core skills. 25 As the CF care model utilizes a multidisciplinary team approach, investigation of the roles of CF nurses, social workers, and other team members in ACP discussions should be pursued. ACP may challenge physicians' time and expertise; thus, optimizing the utilization of other team members in these discussions would be prudent.…”
Section: Discussionmentioning
confidence: 99%
“…Longer and more rigorous PC training/curriculum has been developed for CF providers and has focused on symptom management and difficult conversations; these sessions were well received by participants and (2) significantly improved self-assessed comfort with core skills. 25 As the CF care model utilizes a multidisciplinary team approach, investigation of the roles of CF nurses, social workers, and other team members in ACP discussions should be pursued. ACP may challenge physicians' time and expertise; thus, optimizing the utilization of other team members in these discussions would be prudent.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents (ages [13][14][15][16][17] and adults with CF, family members and CF care team members were recruited for participation.…”
Section: Methodsmentioning
confidence: 99%
“…CF patients and care teams report challenges when discussing the management of CF, 1 including sensitive subjects such as adherence, psychosocial concerns, and prognosis 10–12 . A single‐center study 13 demonstrated the feasibility of improving comfort among members of the CF care team in discussing difficult topics through training in specific communication skills (eg, SPIKES 14 ). However, to date, there have been no nationwide programs to address the need to bolster communication more generally in the CF care setting, and few studies have utilized a multimethod, qualitative approach to elicit CF patient, family member and clinician preferences for communicating when discussing care options, the experience of care, and sustaining daily care.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, both pediatric and adult CF care providers must be prepared to address patient preferences for care near the end of life and to help manage both the physical and emotional aspects of care of a dying patient. Many CF providers may not feel equipped to do so without additional training and support . In order to provide high quality care throughout the lifespan, including end of life, CF care providers must help patients and their family caregivers manage uncertainty, navigate disease progression and choices around management of progressive disease, and communicate wishes for end of life care .…”
Section: End Of Life Carementioning
confidence: 99%
“…Many CF providers may not feel equipped to do so without additional training and support. 45,46 In order to provide high quality care throughout the lifespan, including end of life, CF care providers must help patients and their family caregivers manage uncertainty, navigate disease progression and choices around management of progressive disease, and communicate wishes for end of life care. 47,48 We will highlight important aspects of care of people dying from complications of CF and hope to promote ongoing efforts to enhance end of life care.…”
Section: End Of Life Carementioning
confidence: 99%